2015
DOI: 10.1017/jfm.2015.191
|View full text |Cite
|
Sign up to set email alerts
|

Near-wall rising behaviour of a deformable bubble at high Reynolds number

Abstract: The dynamics of a large deformable bubble (Re ∼ O(10 3 )) rising near a vertical wall in quiescent water is experimentally investigated. The reference (without the wall) rising path of the considered bubble is a two-dimensional zigzag. For a range of wall configurations (i.e. initial wall distance and boundary condition), using high-speed shadowgraphy, various rising behaviours such as periodic bouncing, sliding, migrating away, and non-periodic oscillation without collisions are measured and analysed. Unlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 66 publications
0
12
2
Order By: Relevance
“…Although it was claimed that the gas bubbles introduced into the flow would enhance the sustainability and amount of plastron and hence reduce the drag on the random-roughness SHPo surface (Fukuda et al 2000;Du et al 2017), the exact mechanism of interaction was not found, although one can speculate the bubbles in the flow replenish the air pockets. Jeong and Park (2015) experimentally showed that rising air bubbles attach and slide on a SHPo vertical wall without merging with the plastron unless the thin water layer present between the surface and bubble ( d l ) becomes thinner than O(1) μm. Following the theoretical relation of d l ∼ ( l l v l v g ) 0.5 d 2 g −1 Δt −0.5 for the critical thickness in their study ( l : viscosity of water, l : density of water, v l : velocity of water, v g : velocity of bubble, d g : bubble diameter, : surface tension of water, and Δt : time duration at which the bubble resides on the surface), the product of v l v g ∕Δt should be smaller than O(1) for the bubble of d g ∼ O(100) μm, for example, to have a chance to merge into the air layer on the SHPo surface.…”
Section: Further Issues For Practical Applicationsmentioning
confidence: 99%
“…Although it was claimed that the gas bubbles introduced into the flow would enhance the sustainability and amount of plastron and hence reduce the drag on the random-roughness SHPo surface (Fukuda et al 2000;Du et al 2017), the exact mechanism of interaction was not found, although one can speculate the bubbles in the flow replenish the air pockets. Jeong and Park (2015) experimentally showed that rising air bubbles attach and slide on a SHPo vertical wall without merging with the plastron unless the thin water layer present between the surface and bubble ( d l ) becomes thinner than O(1) μm. Following the theoretical relation of d l ∼ ( l l v l v g ) 0.5 d 2 g −1 Δt −0.5 for the critical thickness in their study ( l : viscosity of water, l : density of water, v l : velocity of water, v g : velocity of bubble, d g : bubble diameter, : surface tension of water, and Δt : time duration at which the bubble resides on the surface), the product of v l v g ∕Δt should be smaller than O(1) for the bubble of d g ∼ O(100) μm, for example, to have a chance to merge into the air layer on the SHPo surface.…”
Section: Further Issues For Practical Applicationsmentioning
confidence: 99%
“…By changing from rising bubbles to sliding ones, Maxworthy [9] performed one of the first studies of the dynamics of a bubble sliding under an inclined surface, explaining that sliding bubbles differed from free rising bubbles in that they only experienced a predominant buoyancy force [9,[26][27][28][29]. Depending on the angle of inclination of the upper wall and the bubble size, several behaviors of bubbles can be found: (i) bouncing for low angles of α < 5° [29], (ii) sliding for intermediate angles 5°< α < 80° [26,27,30], or (iii) steady bouncing of constant amplitude for high angles [18,31]).…”
Section: Introductionmentioning
confidence: 99%
“…The gravitational potential energy is neglected as well. The kinetic energy of lateral motion ( E kx ) reads (Jeong and Park 2015;Newman 1977) where is the density of the surrounding liquid. R 1 and R 2 are the semi-major and minor axes of bubbles, respectively.…”
Section: Drag and Lift Coefficientsmentioning
confidence: 99%